Facilitation, Coordination, and Trust in Landscape-Level Forest Restoration. Issue 1 (20th April 2017) - Coleman, Kimberly; Stern, Marc J; Widmer, Jocelyn
Abstract: Collaborative forest management efforts often encounter challenges related to process and stakeholder relationships. To address these challenges, groups may employ the services of coordinators and facilitators who perform a range of tasks in support of the collaborative. We sought to understand differences between facilitation and coordination in terms of trust creation and maintenance. We conducted case studies in four collaborative groups, one with a facilitator and three with coordinators. We highlight the trust-building practices unique to the facilitator and discuss the potential implications for future collaborative groups.